Sử dụng Rietveld trong phân tích cấu trúc Fe3O4 được tổng hợp bằng phương pháp thủy nhiệt - Thái, Bùi Thị; Hoàn, Nguyễn Xuân (Vietnam Journal of Chemistry, 2014)
Magnetite powders have been prepared by hydrothermal reaction of Fe2+/Fe3+ in the alkaline solution at 1500C. X-ray powder diffraction pattern indicates that the product is single-phase magnetite in an inverse spinel structure. Its composition and crystal structure is determined by Rietveld refinement method combined with Differential Thermal Analysis and Thermal Gravimetry Analysis (DTA-TG). Crytal data: Fe3O4, cubic, Fd-3m, a = 8.379(7) Å, V = 588.43 Å3.